2003
DOI: 10.1017/s0144686x03001314
|View full text |Cite
|
Sign up to set email alerts
|

Combining work and family life: the pension penalty of caring

Abstract: This paper uses work and caring history information from the British Family and Working Lives Survey (1994/5) to examine the provision of family care and its impact upon the employment and the subsequent state and private pension entitlement among mid-life men and women. Combining paid employment with care-giving was not an option for a significant minority of women with caring responsibilities in mid-life. One-in-five mid-life women who have ever had caring responsibilities reported that, upon starting caring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 1 publication
3
77
0
2
Order By: Relevance
“…Indirect or direct financial support has been developed as a way to compensate carers. The reduced labour market participation associated with informal caring has also been recognised, as well as its associated long-term consequences for pensions [6,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Indirect or direct financial support has been developed as a way to compensate carers. The reduced labour market participation associated with informal caring has also been recognised, as well as its associated long-term consequences for pensions [6,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The retired individuals who experience health issues are most likely to be economically disadvantaged. Meanwhile, individuals with the need to take care of family members are less likely come back to labor market (Evandrou & Glaser, 2003).…”
Section: Age Related Factors and Demographic Characteristicsmentioning
confidence: 99%
“…The mechanisms which she considered included access to schemes, basis of benefit calculation, number of coverage years, credits for unpaid care work (for children and other family members), the extent to which benefits derive from marriage alone, and universalism versus means testing. She concluded that whilst the UK basic state pension was fairly gender neutral (and here, she possibly underestimated its gender bias, see Evandrou and Glaser (2003)), the UK state earnings related scheme was highly discriminatory, compared with other countries. Ginn (2004) extended this framework to consider the role of private pensions in the system.…”
Section: Engendering Pensions Analysis In the Ukmentioning
confidence: 99%